2012
DOI: 10.1515/cclm-2012-0083
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability and fecal eosinophil-derived neurotoxin are the best diagnosis tools for digestive non-IgE-mediated cow’s milk allergy in toddlers

Abstract: In this routine diagnosis allergy work-up for CMA in toddlers, the best efficacy was seen for intestinal permeability compared to IgE, IgG, skin prick test and atopy patch test. Moreover, fecal EDN in a single spot sample displayed a similar performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 29 publications
4
49
0
1
Order By: Relevance
“…Accordingly, the levels of fecal EDN may not be sufficiently elevated in samples collected just after ingesting the causative food or at an acute FPIES reaction. On the other hand, levels of fecal EDN before oral food challenges were variable in our patients, which was consistent with a previous report (8). Increased levels of baseline fecal EDN in some patients may be attributable to a direct consequence of previous FPIES episodes or non-specific intestinal inflammation due to previous FPIES episodes.…”
Section: Approval For the Study Was Obtained From The Human Research supporting
confidence: 91%
“…Accordingly, the levels of fecal EDN may not be sufficiently elevated in samples collected just after ingesting the causative food or at an acute FPIES reaction. On the other hand, levels of fecal EDN before oral food challenges were variable in our patients, which was consistent with a previous report (8). Increased levels of baseline fecal EDN in some patients may be attributable to a direct consequence of previous FPIES episodes or non-specific intestinal inflammation due to previous FPIES episodes.…”
Section: Approval For the Study Was Obtained From The Human Research supporting
confidence: 91%
“…The in vivo model still needs to be implemented, as it allows the study of mechanisms of action of probiotics, which are known to be multifactorial, including modulation of the host's microbiota, modulation of the immune system, and also improvement of the barrier function of the gut mucosa. Indeed, probiotic strains may also act in parallel on intestinal permeability, which is increased in allergic children (47). Nebot-Vivinus et al showed that the multispecies probiotic Lactibiane Tolerance increased occluding and ZO-1 expression to prevent the disruption of the epithelial barrier (48), which protects the interaction between enteric bacteria and metabolically associated components that can trigger an immune response (49).…”
Section: Discussionmentioning
confidence: 99%
“…Total DNA from cecal or fecal contents (2 droppings) was extracted using guanidium thiocyanate and the mechanical bead beating method as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
“…Standard curves were obtained from serial dilutions of a known concentration of plasmid DNA containing a 16S rRNA gene insert from each genera or group. The coefficients of correlation between log10 colony-forming units (CFU) and rRNA gene copy numbers for each genera and group were obtained from rrnDB (26), enabling calculation of the number of CFU per gram of cecal content or feces.…”
Section: Methodsmentioning
confidence: 99%